Open questions: How many genes do we have? - Salzberg, Steven L. (BMC Biol, 2018)
Seventeen years after the initial publicationx of the human genome, we still haven’t found all of our genes. The answer turns out to be more complex than anyone had imagined when the Human Genome Project began.